Postural control patterns in gravid women-A systematic review. - Wanda Forczek-Karkosz; Agata Masłoń (PLoS ONE)
Background Postural stability is essential for functional independence in the pregnant population. The contradictions between existing studies and the lack of consistent characteristics in the strategies used by pregnant women for postural control demonstrate the need for further investigation. Objectives The aim was to review the available literature on postural strategies throughout pregnancy in both static and dynamic conditions and to provide an assessment of the quality of these studies in terms of methodological issues to identify the reasons for the inconsistencies in findings between research centers. Methods Literature searches were conducted using PubMed and EBSCOhost Research Databases. The latest search was performed on September 01, 2024. The review was restricted to longitudinal, cross-sectional, case-control, and descriptive studies focused on the effect of pregnancy on the stability of future mothers, with the following criteria: healthy pregnant women and singleton pregnancies. Trials were excluded if they were restricted to multiple pregnancies or considered various kinds of interventions. The methodological quality was evaluated using the criteria proposed by Downs and Black. Data items such as information on study design, characteristics of the study sample, equipment used, stability task performance, and outcome measures were presented. Results The final analysis comprised 22 articles, including a total of 641 pregnant and 296 nonpregnant women. Research results in both static and dynamic conditions are inconclusive, showing either a decrease, no change, or improvement in postural equilibrium as pregnancy advances. Importantly, the results indicate that women in advanced pregnancy may be at increased risk of falling when their vision is compromised. Discussion A lack of homogeneity in the study groups and a small number of longitudinal analyses were observed. The methodologies applied and the postural indices used to measure body sway varied across the studies. Our findings can serve as basic data for health promotion programs to encourage safe daily activities in pregnant women.